2016
DOI: 10.3747/pdi.2014.00333
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Hospitalization after Peritoneal Dialysis Catheter Implantation

Abstract: For the first time, our study analyzed the predictors of unplanned hospitalization after PDC implantation and identified the salient risk factors. Increased focus to identify patients at greatest risk for hospitalization, evaluation of processes of care, and implementation of preventive strategies may be helpful to reduce unplanned hospitalization after catheter insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Peritoneal dialysis (PD) is a commonly used method of renal replacement therapy for ESRD patients. The readmission rates of PD patients were quite high, 15.5–37.4%, as reported in developed countries [ 1 , 4 , 5 ]. Although several studies have investigated the risk factors and prevention strategies of readmission among hemodialysis (HD) patients [ 6 9 ], evidence regarding the prevalence and modifiable risk factors of 30-day readmission among PD patients in developing countries was still limited.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Peritoneal dialysis (PD) is a commonly used method of renal replacement therapy for ESRD patients. The readmission rates of PD patients were quite high, 15.5–37.4%, as reported in developed countries [ 1 , 4 , 5 ]. Although several studies have investigated the risk factors and prevention strategies of readmission among hemodialysis (HD) patients [ 6 9 ], evidence regarding the prevalence and modifiable risk factors of 30-day readmission among PD patients in developing countries was still limited.…”
Section: Introductionmentioning
confidence: 72%
“…Previous studies reported that rehospitalization rates were 15.8–37.5% in HD patients [ 1 , 4 , 6 , 7 , 9 ] and 15.5–37.4% in PD patients [ 1 , 4 , 5 ]. Compared to previous studies, the prevalence of 30-day unexpected rehospitalization in our study was much lower.…”
Section: Discussionmentioning
confidence: 99%
“…PDC implantation and removal are common procedures in ESRD patients. GA-related perioperative cardiopulmonary complications and potential severe neurolog-ical complications due to coagulopathy make neither GA nor neuraxial block a good anesthetic solution for PDC procedures in ESRD patients [2,3]. Therefore, LAI is still a common anesthetic option for PDC procedures in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Open dissection peritoneal dialysis catheter (PDC) implantation or removal is a common procedure in patients with end-stage renal diseases (ESRD) in developing countries [1]. Coexisting cardiopulmonary comorbidities and coagulation disorders make neither general anesthesia (GA) nor neuraxial block an optimal anesthetic solution in ESRD patients [2,3]. Local anesthetic infiltration (LAI) has minimal cardiopulmonary interference and is H.Z.…”
Section: Introductionmentioning
confidence: 99%
“…GA may have inhibitory effects on cardiopulmonary function [8], and the use of GA in patients with ESRD may put them at risk [9]. Our previous observation has also shown that GA is one of the risk factors for all-cause unexpected hospitalization after PDC implantation [10]. It was reported that PDC implantations could also be performed by laparoscopy under LAI with nitrous oxide for pneumoperitoneum [11], but this technique was not widely used.…”
Section: Introductionmentioning
confidence: 99%